Exercise-induced bronchoconstriction in children: Delphi study and consensus document about definition and epidemiology, diagnostic work-up, treatment, and follow-up - Fainardi, Valentina; Grandinetti, Roberto; Mussi, Nicole; Rossi, Arianna; Masetti, Marco; Giudice, Antonella; Pilloni, Simone; Deolmi, Michela; Ramundo, Greta; Alboresi, Stefano; Bergamini, Barbara Maria; Bergomi, Andrea; et al. (Respiratory research, 2024)
Background Exercise-induced bronchoconstriction (EIB) is common in children with asthma but can be present also in children without asthma, especially athletes. Differential diagnosis includes several conditions such as exercise-induced laryngeal obstruction (EILO), cardiac disease, or physical deconditioning. Detailed medical history, clinical examination and specific tests are mandatory to exclude alternative diagnoses. Given the high prevalence of EIB in children and its potential impact on health, sport performance, and daily levels of physical activity, health care professionals should be aware of this condition and able to provide a specific work-up for its identification. The aims of the present study were: (a) to assess the agreement among hospital pediatricians and primary care pediatricians of Emilia-Romagna Region (Italy) about the management of EIB in children and (b) formulate statements in a consensus document to help clinicians in daily clinical practice. Methods According to Delphi method, a panel of specialists scored 40 statements that were then revised and discussed during online meetings to reach full consensus. Statements were then formulated. Results To obtain full consensus, the questionnaire was administered in two rounds after full discussion of the uncertain topics on the basis of the latest evidence on EIB published over the last 10 years. Despite an overall agreement on EIB management, some gaps emerged in the sections dedicated to diagnosis and treatment. Nine summary statements on definition, pathogenesis, diagnostic work-up, treatment, and follow-up were eventually formulated. Conclusions This study describes the knowledge of EIB in a group of pediatricians and highlights gaps and uncertainties in diagnosis and treatment. The creation of statements shared by the specialists of the same area may improve the management of EIB in children. However, more research and evidence are needed to better clarify the best treatment and to standardize the best diagnostic protocol limiting useless examinations but at the same time assuring the best management.